2017
DOI: 10.18632/oncotarget.21912
|View full text |Cite
|
Sign up to set email alerts
|

Curative versus palliative treatments for colorectal cancer with peritoneal carcinomatosis: a systematic review and meta-analysis

Abstract: The objective of this study was to provide an up-to-date summary of the current evidence that may be useful for updating guidelines. We comprehensively searched the published literatures and conferences for studies that compared curative with palliative treatments in colorectal cancer patients with peritoneal metastasis. The primary outcomes considered in this study were three- and five-year overall survival rates. We pooled data across studies and estimated summary effect sizes. Overall, patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Mature lncRNA may be located in the mRNA noncoding regions (3′-UTR or introns area) of their target gene, and may result in complete or incomplete complementary pairing, degradation or inhibition of mRNA translation and post-transcriptional alterations in gene expression. They may also participate in the regulation of cell differentiation, proliferation, apoptosis, and tissue and organ development (5,7,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature lncRNA may be located in the mRNA noncoding regions (3′-UTR or introns area) of their target gene, and may result in complete or incomplete complementary pairing, degradation or inhibition of mRNA translation and post-transcriptional alterations in gene expression. They may also participate in the regulation of cell differentiation, proliferation, apoptosis, and tissue and organ development (5,7,17).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is a malignant tumor caused by multiple factors, including individual genetics and environmental effects. For example, large-scale genetic studies have identified that the occurrence of colorectal cancer is associated with multiple genes abnormal expression and multiple molecular interactions (57), but the studies investigating the molecular mechanism of colorectal cancer incidence are not exhaustive. Therefore, additional studies exploring the pathogenesis of colorectal cancer may provide the theoretical basis for novel clinical anti-tumor drugs (8).…”
Section: Introductionmentioning
confidence: 99%
“…The same systematic review[56] suggests the positive effect of adjuvant chemotherapy on overall survival, despite the heterogeneity of the studies. The most recent publications concur on reporting improvement in median survival with modern versus standard chemotherapy protocols[64], and these authors also agree on the actual approach of M1c as a curable stage for CRC[65]. The clinical value of biological therapies remains uncertain.…”
Section: The Role Of Systemic Chemotherapymentioning
confidence: 95%
“…A large meta-analysis[65] found that intention-to-cure treatments improved overall survival in patients with CRC + PM better than palliative strategies. The risks reported have progressively decreased (recent studies report 1%-5% mortality rates at centers of excellence).…”
Section: Outcomes Of Cytoreductive Surgery Plus Hyperthermic Intrapermentioning
confidence: 99%
See 1 more Smart Citation